Francisco Goya, 1746-1828 on the threshold of modernity - Hagen, Rose-Marie; Hagen, Rainer (Koln, Germany Taschen, 2012)
In 1774 Francisco Goya moved to Madrid. He had been commissioned to design tapestries for the Royal Tapestry Factory of Santa Barbara. His age: 28. He had grown up in the provinces, in Saragossa, where he trained under local artists. He had secured the tapestry commission not because of his striking talent, but through family connections. He had got married the year before his brother-in-law, a well-regarded painter in Madrid, arranged the job for him.

Twice already Goya ad tried to gain a foothold in Madrid, submitting paintings to the Royal Academy of Fine Arts of San Fernando in the hope of being able to study there. On both occasions, in vain.

Designing tapestries was not a highly regarded task, nor was it well paid, but it offered the young artist a start in the big city. And the commissions came directly from the Court. Five years later Goya would be presenting his designs to the king and the crown prince and princess in person and thereby kissing their majesties' hands.

It was the artist's task first to produce designs and then, once these had been approved by the court, to transfer them to cartoons, i.e. canvases in the format of the tapestries to be woven. Tapestries traditionally took their subjects from Greek mythology or the history of Rome, but Goya and other young artists were to offer something new -- scenes not from the past, but from present-day Spain.
FA-3619g - Donated by Pierre Go
Keywords: Goya, Francisco, 1746-1828 -- Catalogs; Painters -- Spain -- Biography; Artists -- Spain -- Biography